2010
DOI: 10.4172/jaa.1000023
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Polysaccharides From Phototrophic Microorganisms Exhibit Antiviral Activities to Vaccinia Virus

Abstract: doi:10.4172/jaa.100002

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 29 publications
1
37
0
1
Order By: Relevance
“…Radonic et al [36] and Chen et al [56] have reviewed the antiviral effects of several sPS on different host cell-lines. Calcium-Spirulan, an intracellular polysaccharide produced by A. platensis , inhibited the replication of several viruses in vitro by inhibiting the penetration of the virus into the different host cells used [40,43].…”
Section: The Polysaccharides From Marine Microalgae: From the Sourmentioning
confidence: 99%
See 1 more Smart Citation
“…Radonic et al [36] and Chen et al [56] have reviewed the antiviral effects of several sPS on different host cell-lines. Calcium-Spirulan, an intracellular polysaccharide produced by A. platensis , inhibited the replication of several viruses in vitro by inhibiting the penetration of the virus into the different host cells used [40,43].…”
Section: The Polysaccharides From Marine Microalgae: From the Sourmentioning
confidence: 99%
“…Calcium-Spirulan, an intracellular polysaccharide produced by A. platensis , inhibited the replication of several viruses in vitro by inhibiting the penetration of the virus into the different host cells used [40,43]. Radonic and co-workers [36] also showed that the polysaccharide released into medium by A. platensis and P. purpureum exhibited antiviral activity in vitro and in vivo against two strains of Vaccinia virus and an Ectromelia virus.…”
Section: The Polysaccharides From Marine Microalgae: From the Sourmentioning
confidence: 99%
“…A high therapeutic index (TI), or selectivity index (SI), is preferable for a drug to have a favorable safety and e cacy pro le. Radonic et al (2010) evaluate the effect of sulphur-containing exopolysaccharides from A. platensis (TKV3). According to their study, anionic polysaccharides from Arthrospira showed antiviral activity against enveloped virus such as VACV (EC 50 (TK V3) = 0.78 µg.mL -1 ) via interactions with viral membrane glycoproteins and thus inhibition of virus binding to host cells.…”
Section: Algae and Antiviral Activitiesmentioning
confidence: 99%
“…Similar to a rational drug design process in which drug-protein interactions are modeled in the computer, the rational probe design described here uses a set of criteria and publicly available bioinformatics software to select the desired probe molecules from libraries comprised of hundreds of thousands of probe molecules [44].Summary data from recent studies provide overwhelming evidence that bioinformatics tools are useful in protein interactions [45] microorganisms provide a large pool of bioactive compounds, and the intensive search for new drugs leads to the identification and structure determination of many novel compounds from these organisms [46].…”
Section: Bioinformaticsmentioning
confidence: 99%